Alexithymia and Treatment Outcome in Anorexia Nervosa: A Scoping Review of the Literature - Gramaglia, Carla; Gambaro, Eleonora; Zeppegno, Patrizia (Frontiers in Psychiatry, 2020)
Alexithymia is of great interest as an outcome predictor of recovery from anorexia nervosa, since it may interfere with both treatment compliance and patients’ ability to benefit from the adopted interventions. For this reason, in the last years new treatment approaches targeting emotion identification, expression and regulation have been applied and tested. Using the PRISMA methodology, we performed a review of the literature about treatment outcome in anorexia nervosa, in terms of changes in alexithymia as assessed by its most commonly used self-report measure, the Toronto Alexithymia Scale (TAS). The Medline and Scopus databases were searched, and articles were included if matching the following criteria: dealing with patients affected by anorexia nervosa, without limits of age; involving the application of any kind of targeted therapy or treatment; assessing alexithymia and the effect of a treatment intervention on alexithymia, using the TAS. Ten studies were eventually included in the review. Overall, according to the selected studies alexithymia levels often remain high even after specific treatment. Further research aimed at a deeper understanding of the actual impact of alexithymia on the outcome of anorexia, as well as exploring alternative treatment strategies for alexithymia in EDs, are warranted.